Effect of heat treatment on structural changes in metastable AlSi10mg alloy - Jordović B.; Nedeljković B.; Mitrović N.; Živanić J.; Maričić A. (Journal of Mining and Metallurgy. Section B: Metallurgy, 2014)
This paper presents a study on structural changes occurring in a rapidly quenched metastable AlSi10Mg alloy during heating cycles within the temperature range from room temperature to 800 K. Measurement of electrical resistivity of a ribbon showed that structural stabilization takes place at temperatures ranging from 450 K to 650 K. The isotherms of the electrical resistivity measured at temperatures 473 K, 483 K and 498 K revealed two stages of structural stabilization i.e. a kinetic process and diffusion process. Measurement of the thermoelectromotive force of the thermocouple made from the investigated alloy and a copper conductor by a mechanical joining was used to determine relative changes in the electron density of states of the quenched sample after successive heat treatments. The same alloy sample was subjected to successive heat treatments at temperatures up to 503 K, 643 K, 683 K and 763 K. The change in the thermopower suggested that each heating was followed by an increase in free electron density in the alloy. Therefore, the abrupt decline in electrical resistivity was induced by an increase in both the mean free electron path and free electron density during the thermal stabilization of the structure. [Projekat Ministarstva nauke Republike Srbije, br. OI 172057: Controlled synthesis, structure and properties of multifunctional materials]